Co-designing with adults with acquired neurological disability in the community: a scoping review protocol. Issue 12 (8th December 2022) - D'Cruz, Kate; Antonopoulos, Stephanie; Rothman, Rebecca; Douglas, Jacinta; Winkler, Di; Oliver, Stacey
Abstract : Introduction: Co-designing healthcare research and health services is becoming increasingly prominent. Co-design invites people with disability to leverage their lived experience knowledge to improve service provision, as well as ensuring meaningful and relevant research. Given the emerging nature of the use of co-design with adults with neurological disability, well-defined guidelines on best practice are yet to be developed. The aim of this scoping review is to synthesise available peer-reviewed literature which investigates the use of co-design in research and/or service development with adults who have an acquired neurological disability and live within the community. The findings of this review will help to guide future co-design practice, ensuring people with acquired neurological disability are best supported and engaged in the process. Methods and analysis: This review will follow methodology proposed by Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis: Extension for Scoping Reviews. Systematic electronic database searches will be conducted between the years 2000 and 2022, via MEDLINE, CINAHL, PsycINFO, Scopus and Embase. Article screening and selection will follow the five-stage framework of Arksey and O'Malley, using Covidence software to support review of each retrieved article by two independent reviewers. Final selected qualitative and/or mixed-methods studies that meet the inclusion criteria will be charted, data collated, summarised and reported. Thematic synthesis will be applied to the qualitative data extracted from these studies. Ethics and dissemination: Ethics approval will not be required to conduct this scoping review. It is the authors' intention for the findings of this scoping review to be made available to relevant stakeholders through open-access peer-reviewed publication and disseminated with other healthcare and research networks via translation pieces, including the development of short video summaries and practice resources.